2011
DOI: 10.1245/s10434-011-2091-7
|View full text |Cite
|
Sign up to set email alerts
|

High Lymph Node Yield is Related to Microsatellite Instability in Colon Cancer

Abstract: BackgroundLymph node (LN) yield in colon cancer resection specimens is an important indicator of treatment quality and has especially in early-stage patients therapeutic implications. However, underlying disease mechanisms, such as microsatellite instability (MSI), may also influence LN yield, as MSI tumors are known to exhibit more prominent lymphocytic antitumor reactions. The aim of the present study was to investigate the association of LN yield, MSI status, and recurrence rate in colon cancer.MethodsClini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
59
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 55 publications
(52 reference statements)
9
59
2
2
Order By: Relevance
“…The current results substantiate previous findings by our group (11) and others (12,13) demonstrating an effect of MSI in determining the actual LN counts after surgery. Both MSI and proximal tumor location appear to be associated with a higher LN harvest, both independently and in combination.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The current results substantiate previous findings by our group (11) and others (12,13) demonstrating an effect of MSI in determining the actual LN counts after surgery. Both MSI and proximal tumor location appear to be associated with a higher LN harvest, both independently and in combination.…”
Section: Discussionsupporting
confidence: 93%
“…However, in a previous cohort, we found that microsatellite instability (MSI) was associated with the total number of LNs harvested (11), which has been confirmed by others (12,13). The aim of the present study was to further investigate MSI and KRAS and BRAF mutations and their relationship to the number of harvested LNs in colon cancer patients.…”
Section: Introductionsupporting
confidence: 60%
See 2 more Smart Citations
“…Galon et al 41 coined the term "immune contexture" to describe the effect of the local host immune reaction in crc. There is a negative association between senescence and decreased nodal count 27 , and possibly a stronger association between comorbidity and diminished immunity 28 ; also, patients with crcs that genomically harbour microsatellite instability have a propensity for right-sided malignancies 42 , higher ln yields 43 , and better overall prognosis 44 . Given those findings, it is entirely plausible that ln yield is the surrogate marker for an immune response that reflects inherent prognosis.…”
Section: Discussionmentioning
confidence: 99%